The Class III Peroxidase gene TaPRX-2A controls grain number per spike in common wheat (Triticum aestivum L.) - Zang, Dongtian; You, Wenjia; Wu, Yangyang; Wang, Pengyue; Wang, Zhiyu; Yang, Qingyun; Chi, Shatong; Su, Peisen (Frontiers in Plant Science, 2025)
Some peroxidases (PRXs) are involved in abiotic stress response. However, to the best of our knowledge, the effects of PRXs on agronomic traits including grain number per spike (GNS), spikelet number per spike (SNS) and spike length (SL) are also largely unknown. In our study, we cloned a wheat PRX gene TaPRX-2A and identified its function in controlling GNS by generating transgenic overexpression lines. The results showed that TaPRX-2A overexpression displayed lower GNS and shorter SL, compared with the wild-type plants. RNA-seq analysis indicated alterations in various pathways including flavonoid biosynthesis, lignin biosynthesis, phytohormone signaling, as well as sucrose and starch biosynthesis. Co-expression analysis showed that transcription factors, such as bHLH, WRKY, and bZIP may be involved in the regulation of various genes associated with these pathways. Our findings provide insights into the mechanisms by which PRXs regulate agronomic traits, illustrating potential applicability in crop improvement programs.